Comparative Analysis of Seven Endogenous Hormones in a Novel Dual-axillary Bud Mutant Genotype of Sugarcane - Kamal Priyananda Wickramasinghe; Jun Mao; Chao-hua Xu; Xiu-qin Lin; Xu-juan Li; Wei Qin; Hong-bo Liu; Xin-long Liu; Faisal Mehdi; Pei-fang Zhao; Xin Lu (Sugar Tech, 2024)
The sugarcane genotype YZ 07-86 is a distinct natural mutant with dual-axillary buds. Exploitation of this valuable trait in sugarcane breeding requires an understanding of the physiological mechanism of dual-axillary bud formation. This experiment determined the contents of indole-3-acetic acid (IAA), abscisic acid (ABA), gibberellins (GA 3 and GA 4 ), and three cytokinins (CKs), namely isopentenyl adenosine (iPA), zeatin riboside (ZR), and dihydrozeatin riboside (DHZR), in the shoot apical meristem tissues of YZ 07-86 and its sister line YZ 07-87, which served as the control genotype. The field experiment followed a completely randomized design with three replications for each genotype. Sampling was done at 5-day intervals, starting 106 days after planting. The ELISA technique was used to measure the contents of endogenous hormones. The study revealed that the mean contents of IAA, GA 3 , GA 4 , DHZR, and iPA were not significantly different ( P > 0.05) among the genotypes. Conversely, in YZ 07-86, the mean ZR content was significantly higher ( P < 0.05), and the mean ABA content was significantly lower than in the control genotype. Moreover, the mean content ratios of ZR/IAA, ZR/ABA, ZR/GA 3 , and ZR/GA 4 were also significantly higher in YZ 07-86. The study concludes that elevated ZR content and an increased ZR/ABA ratio directly contributes to dual-axillary bud formation in YZ 07-86, offering valuable insights for the advancement of sugarcane genotypes.